Geometric and dosimetric evaluation of the differences between rigid and deformable registration to assess interfraction motion during pelvic radiotherapy. (January 2019) - White, Ingrid; McQuaid, Dualta; McNair, Helen; Dunlop, Alex; Court, Steven; Hopkins, Naomi; Thomas, Karen; Dearnaley, David; Bhide, Shree; Lalondrelle, Susan
Highlights: Target motion assessment using rigid and non-rigid strategies significantly differ. Geometric changes are not accounted for in margins using rigid approximation. Rectal volume is moderately correlated with anterior/posterior target motion. Substantial reductions in rectal volume result in underdosing of the target. Abstract: Background and purpose: Appropriate internal margins are essential to avoid a geographical miss in intensity-modulated radiation therapy (IMRT) for endometrial cancer (EC). This study evaluated interfraction target motion using rigid and non-rigid approximation strategies and calculated internal margins based on random and systematic errors using traditional rigid margin recipes. Dosimetric impact of target motion was also investigated. Materials and methods: Cone beam CTs (CBCTs) were acquired days 1–4 and then weekly in 17 patients receiving adjuvant IMRT for EC; a total of 169 CBCTs were analysed. Interfraction motion for the clinical target volume vaginal vault and upper vagina (CTVv) was measured using bony landmarks and deformation vector field displacement (DVFD) within a 1 mm internal wall of CTVv. Patient and population systematic and random errors were estimated and margins calculated. Delivered dose to the CTVv and organs at risk was estimated. Results: There was a significant difference in target motion assessment using the different registration strategies (p < 0.05). DVFD up to 30 mm occurred in the anterior/posterior direction, which was not accounted for in PTV margins using rigid margin recipes. Underdosing of CTVv D95% occurred in three patients who had substantial reductions in rectal volume (RV) during treatment. RV relative to the planning CT was moderately correlated with anterior/posterior displacement (r = 0.6) and mean relative RV during treatment was strongly correlated with mean relative RV at CBCT acquired days 1–3 (r = 0.8). Conclusion: Complex and extensive geometric changes occur to the CTVv, which are not accounted for in margin recipes using rigid approximation. Contemporary margin recipes and adaptive treatment planning based on non-rigid approximation are recommended.